AWARENESS OF FORENSIC ODONTOLOGY AMONG DENTAL PROFESSIONALS - Ijaz Ur Rehman; Arooj ul Hassan; Aina Rizwan; Tehseen Nasir; Ujyala Saleem; Iqra Ahmad (Pakistan Oral & Dental Journal, 2021)
Forensic Odontology is a significant outgrowth of Forensic Medicinal Sciences. It plays a pivotal role in identifying the individual. But awareness regarding Forensic Odontology is less among Dental Professionals. It was a cross sectional, questionnaire-based study. Four Dental Institutes of Lahore were selected for the survey. Ethical approval for this study was obtained from the ethical review committee of the University of Lahore. Participants included an assortment of house surgeons, demonstrators and postgraduate trainees of private dental teaching hospitals. A questionnaire consisting of 15 questions was used as a study tool. There were 40 (16.7%) demonstrators, 55 (22.9%) postgraduate residents and 145 (60.4%) house officers. One hundred seventy nine (74.6%) candidates knew about forensic odontology, 189 (78.9%) thought that forensic odontology is an important part of dentistry, but only 25 (10.3%) learned about forensic dentistry in their institution. 66 (27.6%) knew about cases solved by forensic odontologists, 175 (72.8%) maintained the patient record at the hospital, 121 (50.4%) knew the significance of bite mark pattern of teeth, 177 (73.7%) knew that teeth can serve as a source of DNA. Most of the dental professionals were aware of forensic odontology and its importance but were unaware whether this sulyed is being laugh or not in dental colleges. Moreover, Institutions were not providing enough information regarding Forensic Odontology.
Keywords: Forensic Dentistry; dental surgeons; Dental institutes